2021
DOI: 10.3389/fpsyt.2021.638722
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Microstates in Schizophrenia and Bipolar Disorder

Abstract: Schizophrenia (SCH) and bipolar disorder (BD) are characterized by many types of symptoms, damaged cognitive function, and abnormal brain connections. The microstates are considered to be the cornerstones of the mental states shown in EEG data. In our study, we investigated the use of microstates as biomarkers to distinguish patients with bipolar disorder from those with schizophrenia by analyzing EEG data measured in an eyes-closed resting state. The purpose of this article is to provide an electron direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 78 publications
2
13
0
Order By: Relevance
“…Our study found increased microstate class C and decreased microstate class D in patients with FE-SCH, which is consistent with some previous studies [19,26,31]. Such abnormalities of microstate class C and D have been identi ed in patients with chronic schizophrenia [21,32], individuals with ultra-high risk for psychosis [33,34], and even siblings of patients with schizophrenia [26]. Two meta-analyses [25,26] published in recent years showed similar results that the occurrence of microstate class C increased and the occurrence of microstate class D decreased in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found increased microstate class C and decreased microstate class D in patients with FE-SCH, which is consistent with some previous studies [19,26,31]. Such abnormalities of microstate class C and D have been identi ed in patients with chronic schizophrenia [21,32], individuals with ultra-high risk for psychosis [33,34], and even siblings of patients with schizophrenia [26]. Two meta-analyses [25,26] published in recent years showed similar results that the occurrence of microstate class C increased and the occurrence of microstate class D decreased in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 93%
“…Default mode network is the neural basis of ego [39]; it was found to be activated during internally-oriented mental processes and to play an important role in self-referential thoughts and episodic memory extraction [16,40]. The microstate class C might be generated at the bilateral medial temporal gyrus and the lateral parietal lobe [32], which were found to be associated with self-experience in fMRI studies [41,42]. It was also considered that microstate class C was associated with the activation of the default mode network [16,35], the abnormal activation of which has been repeatedly demonstrated in schizophrenia [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Our study found increased microstate class C and decreased microstate class D in patients with FE-SCH, which is consistent with some previous studies ( 20 , 29 , 34 ). Such abnormalities of microstate class C and D have been identified in patients with chronic schizophrenia ( 19 , 36 ), individuals with ultra-high risk for psychosis ( 37 , 38 ), and even siblings of patients with schizophrenia ( 29 ). Two meta-analyses ( 28 , 29 ) published in recent years showed similar results that the occurrence of microstate class C increased and the occurrence of microstate class D decreased in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Default mode network is the neural basis of ego ( 43 ); it was found to be activated during internally oriented mental processes and to play an important role in self-referential thoughts and episodic memory extraction ( 14 , 44 ). The microstate class C might be generated at the bilateral medial temporal gyrus and the lateral parietal lobe ( 36 ), which were found to be associated with self-experience in fMRI studies ( 45 , 46 ). It was also considered that microstate class C was associated with the activation of the default mode network ( 14 , 39 ), the abnormal activation of which has been repeatedly demonstrated in schizophrenia ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Microstate syntax analysis found altered microstate transition probabilities in LLS. Several studies have reported the presence of abnormal microstate syntax in patients with schizophrenia; however, the results are somewhat inconsistent (23,33,49). It has been suggested that microstate syntax may represent the sequential activation of distinct brain networks.…”
Section: Discussionmentioning
confidence: 99%